2014
DOI: 10.1177/1077801214535105
|View full text |Cite
|
Sign up to set email alerts
|

Victim Participation in Intimate Partner Violence Prosecution

Abstract: Are intimate partner violence (IPV) victims safer if they use the criminal justice system? Concerns about perpetrator retaliation, in the face of data that protection orders can reduce future harm, make it important to understand how victim utilization (calling 911, talking to the prosecutor, and proceeding with prosecution) affects subsequent safety. We hypothesized participation would improve victims' safety, measured by decreases in subsequent IPV-related 911 calls and/or emergency department visits. Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…It is likely that additional sources of information, such as parole officers, family members and others who know the perpetrator, will increase our predictive ability as well. However, involving victims of crime in the criminal justice system may not warrant the increased risk to their safety [47].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that additional sources of information, such as parole officers, family members and others who know the perpetrator, will increase our predictive ability as well. However, involving victims of crime in the criminal justice system may not warrant the increased risk to their safety [47].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, according to Cerulli et al (2014), the victim needs not only protection, but also participation in the process of overcoming abuse, so the least satisfied victims are those whose preferences are not taken into account (Buzawa et al 2017), and the advice and support of the lawyer throughout the process may contribute to this participation. Receiving legal advice lets the women have more information about each step, about the impact of the final verdict, and about the eventual obstacles or protectors that may appear throughout the whole process.…”
Section: Discussionmentioning
confidence: 99%
“…In court, DV victims are often viewed as “reluctant” or “uncooperative” witnesses (e.g., Cerulli et al., : 142). Cattaneo and Goodman () suggested that the process of DV prosecutions has more of an impact than the case outcomes on the perpetrators’ recidivism.…”
Section: Nonpolice‐related Research Findings On Domestic Violence In mentioning
confidence: 99%
“…For example, Cerulli et al. () found that DV prosecutor–victim contact prior to the court case was the key to deterring police‐reported DV recidivism, regardless of whether the victim wanted the prosecutor to proceed with or drop charges. These findings have led to the development of specialized DV courts over the past few decades.…”
Section: Nonpolice‐related Research Findings On Domestic Violence In mentioning
confidence: 99%